11+3x=-4-2x=x=

Simple and best practice solution for 11+3x=-4-2x=x= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 11+3x=-4-2x=x= equation:



11+3x=-4-2x=x=
We move all terms to the left:
11+3x-(-4-2x)=0
We add all the numbers together, and all the variables
3x-(-2x-4)+11=0
We get rid of parentheses
3x+2x+4+11=0
We add all the numbers together, and all the variables
5x+15=0
We move all terms containing x to the left, all other terms to the right
5x=-15
x=-15/5
x=-3

You can always share this solution

See similar equations:

| 38.95=22.50+s | | 2-x/0.3=14 | | 22+5x=-8-x=x= | | 13=u-22 | | 18-4x=-9-x=x= | | 128+x=350 | | 8-2x=11+x=x= | | Y=1/4x+10 | | 0.1x=+14 | | (h-8^2=0 | | 25+20x=-5+5x=x= | | 2x+4x+3=9x–18 | | 2q^+8q=3 | | (2x-3)^2-(5x+1)^2=0 | | x2–8x+16=4 | | x-10/20+x/20=1 | | 1x(20)+10(319-1x)=5860 | | -b^2+6b-8=0 | | -3(x+8)+33=14-4x | | 4x+8=9-x | | 10+12x=-8+6x=x= | | 12-y=48 | | x2?6x+9=16 | | x^2?6x+9=16 | | ?x–9?–5=12 | | 6c–24=12 | | 16-2x=-4-7x=x= | | 5(2x?8)=30 | | Y=(1)x | | 3x-4=4-(8x3x) | | 21-3x=-7-10x=x= | | (5x?15)×(9x+18)=0 |

Equations solver categories